2017
DOI: 10.1186/s13028-017-0292-1
|View full text |Cite|
|
Sign up to set email alerts
|

Liver morphometrics and metabolic blood profile across divergent phenotypes for feed efficiency in the bovine

Abstract: BackgroundFeed costs are a major expense in the production of beef cattle. Individual variation in the efficiency of feed utilization may be evident through feed efficiency-related phenotypes such as those related to major energetic sinks. Our objectives were to assess the relationships between feed efficiency with liver morphometry and metabolic blood profile in feedlot beef cattle.MethodsTwo populations (A = 112 and B = 45) of steers were tested for feed efficiency. Blood from the 12 most (efficient) and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…On the other hand, lower cholesterol concentrations in the efficient pregnant heifers may be related to differences in cholesterol metabolism and diminished lipogenesis. Other studies in young bulls [ 6 ] and feedlot steers [ 49 ] reported reduced cholesterol levels in cattle with higher feed efficiency, supporting our results. This observation could relate to a down-regulation of enzymes involved in the cholesterol synthesis, or a reduction in substrate availability because acetate is required to generate reducing equivalents, or an increase in biliary excretion of cholesterol [ 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, lower cholesterol concentrations in the efficient pregnant heifers may be related to differences in cholesterol metabolism and diminished lipogenesis. Other studies in young bulls [ 6 ] and feedlot steers [ 49 ] reported reduced cholesterol levels in cattle with higher feed efficiency, supporting our results. This observation could relate to a down-regulation of enzymes involved in the cholesterol synthesis, or a reduction in substrate availability because acetate is required to generate reducing equivalents, or an increase in biliary excretion of cholesterol [ 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…Paula et al [ 33 ] demonstrated that the most efficient lambs had lower serum albumin concentrations. This phenomenon was also identified in the plasma of beef steers [ 34 ]. Another study by Connell et al [ 35 ] showed a relationship between serum albumin levels and DMI in sheep.…”
Section: Discussionmentioning
confidence: 78%
“…However, the size of epithelium cells in the ventral blind sac and across sacs was larger in efficient animals. Montanholi et al (2017) found a larger hepatocyte size in the livers of efficient animals with respect to the portal triad and central vein, but no difference in liver weight. Nevertheless, Richardson et al (2001), Sainz et al (2006), Gomes et al (2012), Meale et al (2017), and Fidelis et al (2017) could not find difference between RFI and visceral organ traits.…”
Section: Discussionmentioning
confidence: 77%